Business Development Acceleration through MSME-Friendly Financial Institutions in Wetland Areas in Banjarmasin City - Noor Hidayati, Noor Hidayati; Hidayat, Rizki Muslim (PT. Hanken SUkses Jaya, 2024)
The aim of this research is to create acceleration in business development through financial institutions that are friendly to MSMEs. The specific objectives are to analyze the characteristics of MSME-friendly financial institutions in the wetland areas of Banjarmasin City, to identify the profile of MSME-friendly financial institutions in the wetland areas of Banjarmasin City, and to analyze business development through MSME-friendly financial institutions in the wetland areas of Banjarmasin City. The research method utilizes a quantitative approach with research instruments and is supported by in-depth interviews to map out issues and policies in MSME development as well as existing financial institutions in Banjarmasin City in credit disbursement and assistance to MSMEs. The research results are as follows: 1) Data processing results of productive business criteria with higher final weight values, and dominance compared to other aspects/criteria by experts, thus it can be concluded that productive business aspects/criteria can be considered as one of the accelerations in business development through MSME-friendly financial institutions in Banjarmasin City. Furthermore, financing pattern aspects/criteria with a final weight value of 23.7%, and financing schemes with a final weight value of 20.8%. 2) Data processing results of AHP using Expert Choice 11 show that the priority/alternative financial institutions with higher final weight values with a weight value of 31.7%, and dominant compared to other priority/alternatives by experts, thus it can be concluded that priority/alternative accelerations for development can be considered as one of the acceleration strategies for business development through MSME-friendly financial institutions in Banjarmasin City. Furthermore, priority/alternative accelerations for development with a final weight value of 26.6%, business management with a final weight value of 24%, and credit disbursement mechanisms with a final weight value of 15.7%